Jesús Astigarraga, «A Unifying Enlightenment. Institutions of Political Economy in Eighteenth-Century Spain (1700-1808)» - Muñoz Sempere, Daniel (Cuadernos de Ilustración y Romanticismo, 2022)
Reseña bibliográfica.